EMPOWERING MSMEs: ENHANCING CAPABILITIES WITH MANAGERIAL SKILLS, STRATEGIC ALLIANCES, AND DIGITAL MARKETING TRAINING - Pitoyo, Djoko; Nasrudin, Inayati; Nurwathi, Nurwathi (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia portray a crucial role in the economy but face challenges in maximizing their capabilities due to limited resources and strategic alliances. This study aims to explore how managerial skills can capture strategic alliance opportunities to increase MSMEs' capabilities, moderated by digital marketing training. Employing a quantitative approach using an explanatory survey design, the population consists of 5,760 MSMEs, and data was collected from 360 MSMEs, using proportional random sampling, in Greater Bandung across four sectors: culinary, fashion, handicraft, and beauty & health. Data analysis was conducted by Partial Least Square (PLS) to examine the relationships between variables. Results indicate that managerial skills significantly influence both strategic alliances and MSME capabilities, and that digital marketing training further enhances these capabilities. However, digital marketing training does not moderate the relationship of strategic alliance and MSME capabilities. The study’s implications highlight the importance of investing in managerial skills development and digital marketing training to foster strategic alliances and enhance MSME capabilities. JEL: L26, M31, M53.